Medical and Economic Implications of Prolonged Mechanical Ventilation and Expedited Post–Acute Care - Cox, Christopher E.; Carson, Shannon S. (Seminars in Respiratory and Critical Care Medicine, 2012)
This article describes the increasingly common phenomenon of prolonged mechanical ventilation in the context of the transition between the acute care hospital and post–acute care. Prolonged mechanical ventilation or chronic critical illness is associated with hospital mortality in the range of 20 to 40%, with median hospital length of stay ranging from 14 to 60 days. Fewer than 10% of patients are discharged home, and most hospital survivors require institutionalized post–acute care in the form of long-term acute care, skilled nursing facilities, or inpatient rehabilitation. Acute hospital readmission is common. Because of prolonged functional disabilities and multiple underlying comorbid conditions, overall 1 year mortality for prolonged mechanical ventilation patients ranges from 50 to 60%. Survivors experience significant functional limitations. The prolonged institutional care and poor long-term outcomes of these patients bring into question the cost-effectiveness of prolonged mechanical ventilation after acute illness, especially for patients with poor long-term prognoses. New measures to facilitate assessments of long-term prognosis and improve communication with surrogate decision makers may reduce the amount of ineffective care for some patients requiring prolonged mechanical ventilation.
Keywords: prolonged mechanical ventilation; prognosis; health care costs